University in times of pandemic. University students’ experience in Spain - FERRÁNDEZ-BERRUECO, Reina; MARQUÉS ANDRÉS, Mercedes; SÁNCHEZ-TARAZAGA, Lucía; RUIZ BERNARDO, Paola (Utopía y Praxis Latinoamericana, 2021)
On 14 March 2020, an emergency teaching period began. Faculty and students were faced with an unprecedented situation. This survey study shows how higher education students rated this experience and which dimensions were the most important in their assessment. In general, the experience was negative, with the academic dimension being responsible for this assessment. The conclusion brings us back to Bologna and the need to enhance student autonomy. Something that seems to have been forgotten.